2016
DOI: 10.1002/zaac.201600071
|View full text |Cite
|
Sign up to set email alerts
|

A First‐Principles Study on the Electronic, Vibrational, and Thermodynamic Properties of Jadeite and its Tentative Low‐Density Polymorph

Abstract: The high-pressure clinopyroxene mineral jadeite (chemical composition NaAlSi 2 O 6 ) was studied by density-functional theory with respect to its electronic, vibrational, and thermodynamic properties, correctly reproducing the available experimental data. At a larger-thannormal volume, however, a low-density alumosilicate phase with tetrahedral instead of octahedral Al-O coordination was identified. This low-density phase was investigated theoretically, too, and the results were compared to jadeite and experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…As expected, only at quite small molar volumes, which correspond to higher pressure, these modifications become energetically favorable. A similar observation as for the enstatite polymorphs has recently been made for the case of jadeite (Stoffel et al, 2016) where such a low-density polymorph was found to be similar to the isochemical glass phase with jadeite composition in terms of its macroscopic properties.…”
Section: Quantum Chemical Calculationssupporting
confidence: 80%
See 1 more Smart Citation
“…As expected, only at quite small molar volumes, which correspond to higher pressure, these modifications become energetically favorable. A similar observation as for the enstatite polymorphs has recently been made for the case of jadeite (Stoffel et al, 2016) where such a low-density polymorph was found to be similar to the isochemical glass phase with jadeite composition in terms of its macroscopic properties.…”
Section: Quantum Chemical Calculationssupporting
confidence: 80%
“…Using Helgeson's (Helgeson and Kirkham, 1976) value of the partial molar volume of H 2 O of approximately 8 cm 3 /mol, this yields a molar volume for dehydrated analcime of approximately 88.9 cm 3 /mol, which is in fair agreement with the value of the hypothetical structure identified; this also matches with the experimentally determined molar volume of the isochemical glass. Previous DFT calculations (Stoffel et al, 2016) as well as calorimetric values showed that both dehydrated analcime and the isochemical glass display nearly identical heat capacity c p .…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%